Addressing Economic Barriers of Farmer Families’ Education - Amandaria, Riri; Mario, Mario (LPPM Universitas Madako Tolitoli, 2024)
Education is crucial for the development of children, especially those living in rural farming communities in developing nations. However, these children encounter various obstacles that impede their access to quality education. This abstract delves into the challenges posed by inadequate educational infrastructure, economic limitations within farming families, and a lack of parental understanding regarding the value of education for rural farming children in Indonesia. These hurdles result in less-than-optimal educational outcomes and decreased participation in schooling among this vulnerable demographic. To tackle these issues, it is imperative to engage in collaborative endeavors involving governmental bodies, educational establishments, and the local populace. By investing in educational infrastructure, ensuring an equitable distribution of teachers, offering financial aid to farming families, and enhancing awareness about the importance of education, a more inclusive and fair educational atmosphere can be established. Through the joint implementation of these suggestions, rural farming children can be empowered with equal opportunities to access high-quality education and secure a more promising future.